Pengendalian Kualitas Produk Menggunakan Lean Six Sigma dan Fuzzy FMEA Dalam Upaya Menekan Kecacatan Produk - Muvidah, Nada Iman; Yunitasari, Elly Wuryaningtyas; Kusmendar, Kusmendar (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Quality control is a process used to ensure the level of quality in a product or service so as to lead to customer satisfaction. UMKM Eko bubut is a UMKM that produces wooden handicrafts with product marketing that reaches the international market. In the problem of product quality control at UMKM Eko Bubut, it was found that there were five types of defects, namely wavy, rough, perforated, cracked, and broken defects. In addition, it was found that there was wastage that occurred which had an effect on disability. Solving quality control problems at UMKM Eko Bubut is by using lean six sigma to identify the sigma level and fuzzy FMEA is used to determine the main priority for repairs to the causes of production defects that occur. The results of the calculation of the defect level of bowl products, it was found that the types of defects were wavy (55.06%), rough (28.29%), perforated (7.82%), cracked (7.22%) and broken (1.61%). The identification results of the waste that occurs are waste defects (28.1%), waste overproduction (17.7%), waste waiting (16.2%), waste motion (16.0%), waste inventory (10.75%), waste transportation (6.55%), and over-processing (4.9%). The results of calculating the DPMO value obtained an average sigma of 3.27 with a DPMO value of 38890.41. This shows that for every 1,000,000 production, there is a possibility that there will be product defects in as many as 38,890 products. Factors that affect product defects are humans, raw materials, methods, machines, and the environment.